Influence of tuber infection, wetting durations, crop age and incubation period on late blight development in potato under Punjab conditions - C. MOHAN, T.S. THINO* and (Indian Phytopathology, 2008)
The developmental behaviour of potato late blight caused by Phytophthora infestans (Mont.) de Bary in the N-W plains was investigated. Infection in the vicinity of buds on tubers produced very few diseased shoots which were soon killed. Infected tubers rotted in the field soil when planted early in the season in September due to high soil temperature (> 40°C) and served as primary inoculum source only when planted in second week of October onwards. Early planting of infected tubers gave rise to patchy appearance of the crop in the field. Early planted crop exhibited less disease severity than late planted crop but the disease levels were similar after 30 days of inoculation. A minimum of 2h of leaf wetness was required for infection at 10-20 °C and no infection occurred at 25°C. Wetness duration from 10.00 to 16.00 hours in the field led to maximum disease severity. On susceptible cv. Kufri Chandramukhi, incubation period mostly varied between 5-6 days in November to 10-12 days in December - January and again decreased in February and it showed negative correlation with minimum temperature. On moderately resistant cvs. Kufri Jyoti and Kufri Badshah incubation period ranged from 10-21 days during November to February.